Peran Lembaga Perlindungan Saksi Dan Korban Dalam Memberikan Perlindungan Hukum Terhadap Korban Tindak Pidana Kekerasan Seksual - Roy Andi Siregar; Tofik Yanuar Chandra; Achmad Fitrian (UIN Fatmawati Sukarno Bengkulu, 2023)
Abstract: A criminal act is an act that is prohibited by a rule of law, which prohibition is accompanied by threats or sanctions in the form of certain crimes, for anyone who violates the prohibition. It can also be said that a criminal act is an act which is prohibited by a rule of law and is punishable by punishment, as long as it is kept in mind that the prohibition is aimed at an act, namely a situation or an event caused by a person’s behavior, while the criminal threat is directed at a person who causes a crime. that incident. Between prohibition and punishment there is a close relationship, because between the incident and the person who caused the incident there is also a close relationship, which cannot be separated from the others. Sexual intercourse is any act that ranges from sexual harassment to the act of forcing someone to have sexual intercourse without the victim’s consent or when the victim does not want it, and/or having sexual intercourse in ways that are unnatural or not liked by the victim and distances him from his sexual needs. Article 5 of Law Number 31 of 2014 concerning Amendments to Law Number 13 of 2006 concerning Protection of Witnesses and Victims. Witnesses and Victims are entitled to: obtain protection for personal safety, family. Keywords: Crime, Sexual Violence, Witness